Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

688_16302_Question.jpg

Grade:12

1 Answers

vikas askiitian expert
509 Points
10 years ago

a,b,c are terms of ap then

b-a = c-b

 2b = a+c      ..........1

log2 , log2x-1 , log2x+3 are in ap so

2log2x+1 = log2+log2x+3

loga + logb =logab

now expression is

log(2x+1)2 = log[2(2x+3)]

 (2x+1)2 = 2(2x+3)

put 2x = t

(t+1)2 = 2(t+3)

 t = 1,5

2x = 1       or   2x = 5   , x = log5/log2

x = 0 cannot be the solution so x = log5/log2 is the required solution

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free